Adsorption of fluids on solid surfaces: A route toward very dense layers - Sartarelli, Salvador Andrés (2012)
Adsorption of Xe on single planar walls is investigated in the frame of a density functional theory. The strength of the adsorbate-substrate attraction is changed by considering surfaces of Cs, Na, Li, and Mg. The behavior is analyzed by varying the temperature T (between the triple point Tt and the critical Tc) and the coverage image. The obtained adsorption isotherms exhibit a variety of wetting situations. Density profiles are reported. It is shown that for strongly attractive surfaces the adsorbed liquid becomes very dense reaching densities characteristic of solids.